2018
DOI: 10.4103/aja.aja_30_17
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide sensitizes prostate cancer cells to TRAIL-induced apoptosis

Abstract: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) is a promising agent for anticancer therapy. The identification of small molecules that can establish the sensitivity of prostate cancer (PCa) cells to TRAIL-induced apoptosis is crucial for the targeted treatment of PCa. PC3, DU145, JAC-1, TsuPr1, and LNCaP cells were treated with Andrographolide (Andro) and TRAIL, and the apoptosis was measured using the Annexin V/PI double staining method. Real time-polymerase chain reaction (PCR) and Western b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Similar mechanism has been reported in prostate cancer cells. TRAIL and andrographolide combinatorially induced regression of tumors in mice xenografted with prostate cancer cells [ 54 ]. Andrographolide effectively reduced NF-ҡB/p65 subunit and stimulated the expression of DR4 and DR5 in bladder cancer cells [ 55 ].…”
Section: Regulation Of Trail Pathwaymentioning
confidence: 99%
“…Similar mechanism has been reported in prostate cancer cells. TRAIL and andrographolide combinatorially induced regression of tumors in mice xenografted with prostate cancer cells [ 54 ]. Andrographolide effectively reduced NF-ҡB/p65 subunit and stimulated the expression of DR4 and DR5 in bladder cancer cells [ 55 ].…”
Section: Regulation Of Trail Pathwaymentioning
confidence: 99%
“…Accumulating evidence has demonstrated additional effects of andrographis with some of the conventional chemotherapeutic drugs. For instance, andrographis potentiated the antitumor effects of topotecan, paclitaxel, cisplatin and gemcitabine in acute myeloid leukemia, non-small cell lung cancer, oral squamous cell carcinoma and pancreatic cancer, respectively [33][34][35][36] . Previous studies have also demonstrated the anti-proliferative and chemo-sensitizing properties of andrographis in CRC cells 37,38 .…”
Section: Discussionmentioning
confidence: 99%
“…F.) Wall. Ex Nees (Family: Acanthaceae; Islam, 2017), exhibits various biological activities such as anti-inflammatory (Li et al, 2017;Wang et al, 2019), antivirus (Paemanee et al, 2019;Uttekar et al, 2012), anticancer (Peng et al, 2018;Reabroi et al, 2018;Wei et al, 2018), liver protection (Abdullah & Ismail, 2018), cardiovascular (Wu et al, 2018), and neuroprotective effect (Tao et al, 2018) and is mainly used in clinic for treating cold, fever, gastroenteritis, and upper respiratory tract. The nephrotoxicity of TCM has been reported since the 1980s (Upreti et al, 1989) and has attracted widespread attention (Feng et al, 2018;Song et al, 2018;Vanherweghem et al, 1993).…”
Section: Introductionmentioning
confidence: 99%